A comparison of response interruption and redirection and competing items on vocal stereotypy and appropriate vocalizations. Issue 1 (7th July 2019) - Shawler, Lesley A.; Dianda, Mia; Miguel, Caio F.
Abstract : The current study compared the reductive effects of response interruption and redirection (RIRD) and competing items (including sound‐producing and nonsound‐producing toys) on the vocal stereotypy exhibited by two children diagnosed with Autism Spectrum Disorder. Sound‐producing toys reduced vocal stereotypy relative to nonsound‐producing toys and RIRD reduced stereotypy and increased rates of appropriate vocalizations to a greater extent than providing competing items. These findings replicate and extend previous literature suggesting that RIRD and sound‐producing competing items are effective methods to treat vocal stereotypy.